Surveillance capitalism in America - Lauer, Josh (Professor of communication); Lipartito, Kenneth, 1957- (Hagley perspectives on business and culture., 2021)
"Surveillance Capitalism in America offers a crucial historical perspective on the intimate relationship between surveillance and capitalism. While surveillance is often associated with governments, today the role of the private sector in the spread of everyday surveillance is the subject of growing public debate. Tech giants like Google and Facebook are fueled by a continuous supply of user data and digital exhaust. Surveillance is not just a side effect of digital capitalism; it is the business model itself, suggesting the emergence of a new and more rapacious mode of capitalism: surveillance capitalism."--